2020
DOI: 10.1111/jnu.12588
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Improving or Worsening the State of Frailty: A Secondary Data Analysis of a 5‐Year Longitudinal Study

Abstract: Purpose This study aims to examine the frailty transition patterns of older adults recruited from both community and residential care settings within a 5‐year period, and to identify the physical and psychosocial factors associated with the transitions. Design This study is a secondary data analysis of a longitudinal study for tracking the change of health status of older adults 60 years of age or older. Participants who had undergone at least two assessments during 2013–2017 were selected for analysis. Guided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 56 publications
2
24
0
Order By: Relevance
“…Figure 1 summarises the results of the systematic search of the literature. Five thousand and thirty (5030) articles were screened for eligibility, but only 16 fulfilled criteria for inclusion and these resulted in 13 cross-sectional and 5 longitudinal datasets (two studies reported both cross-sectional and longitudinal data [ 27 , 28 ]). Among these, two studies [ 29 , 30 ], and the longitudinal component of one study [ 27 ] did not include sufficient data for meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 summarises the results of the systematic search of the literature. Five thousand and thirty (5030) articles were screened for eligibility, but only 16 fulfilled criteria for inclusion and these resulted in 13 cross-sectional and 5 longitudinal datasets (two studies reported both cross-sectional and longitudinal data [ 27 , 28 ]). Among these, two studies [ 29 , 30 ], and the longitudinal component of one study [ 27 ] did not include sufficient data for meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Five thousand and thirty (5030) articles were screened for eligibility, but only 16 fulfilled criteria for inclusion and these resulted in 13 cross-sectional and 5 longitudinal datasets (two studies reported both cross-sectional and longitudinal data [ 27 , 28 ]). Among these, two studies [ 29 , 30 ], and the longitudinal component of one study [ 27 ] did not include sufficient data for meta-analysis. Fourteen studies were included in the quantitative analysis with 12 sets of cross-sectional data (including 12,313 participants) and three sets of longitudinal data (including 3042 participants).No case-control studies met our inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…In previous longitudinal studies, greater physical activity decreased frailty over time. 26,27 Physical activity can reduce the effect of aging by increasing physical capacity and help recover from acute disease and thus positively help prevent frailty. 28 The present study also showed that low depressive symptoms were a protective factor in pre-frail improvement.…”
Section: Discussionmentioning
confidence: 99%
“…The research team conducted secondary analysis of health status data obtained from community and nursing home dwelling adults (N=306) aged 60 years or older living in Hong Kong. 4 Using a complex correlational design, data from two annual assessments were analysed to describe participants' frailty characteristics and compare the changes between assessments. Demographic, physical and psychological factors were used to categorise participants as frail, pre-frail and robust.…”
Section: Methodsmentioning
confidence: 99%
“…The retrospective health status data 4 accessed was a convenient source of frailty factors; however the findings may not represent the wider Hong Kong ageing population or be transferrable to other ageing populations. The importance of utilising existing health data sets is evident.…”
Section: Commentarymentioning
confidence: 99%